Immediate Neuroplastic Changes in the Cortex After iTBS on the Cerebellum of Stroke Patients: A Preliminary fNIRS Study - Shuo Xu; Shaofan Chen; Ningling Chen; Zhengcong Zhang; Chenfang Liang; Hongwei Huang; Huijie Zou; Haoqing Jiang (Neural Plasticity)
Conclusion: The application of iTBS to the cerebellum significantly enhances the activation of cognitive and motor areas in the cerebral cortex. Additionally, improved FC between brain regions and increased spontaneous neuronal activity were observed following stimulation. These findings reveal the potential mechanisms by which cerebellar iTBS may facilitate functional recovery in stroke patients.